Kemampuan Manajerial Kepala Smk Program Keahlian Otomotif Dan Keterserapan Lulusan Di Dunia Kerja - Prihantoro, C Rudi (INVOTEC, 2010)
In an effort to equip students with skills and skills in accordance with the needs of theautomotive world of work, school principals must have a good strategic plan related to student learning,teacher performance, materials of teaching materials, relationships with business / industry. In thatcontext, this research is conducted. With qualitative and descriptive survey method kuantitatf, researchresults show that school leadership has a high managerial skills proved to increase cooperation withindustry and graduates in the world of work absorption.